Analysis of Factor Affecting Milenial Generation Employee - Luh Kardini, Ni; Yulia, Rasty; Andriani, Hertya (Journal of Management, 2024)
Millennial Generation Engagement, Organizational Commitment, and Job Satisfaction are significant elements in the industrial work area. This study aims to investigate the influence of different motivational factors on the collaboration and communication bonds between leaders and employees, and the effects of non-financial incentives and Millennial Generation engagement on Organizational Commitment and employee job satisfaction at PT. Kahatex Indonesia. This study used a purposive sampling method to select 87 respondents from employees of the electronics manufacturing industry in Indonesia. The collected information was analyzed using Structural Equation Modeling with the support of SmartPLS 3.0 analysis tools. The results of the study show that non-financial incentives have a significant effect on employee work motivation. That is, the provision of non-financial incentives by industry leaders contributes to increasing employee Organizational Commitment. However, the findings of the study also show that Millennial Generation engagement does not have a significant effect on employee work motivation. This means that the Millennial Generation engagement between leaders and employees and between employees does not directly affect their level of Organizational Commitment. Furthermore, this study also found that Organizational Commitment has a significant effect on employee job satisfaction.